Effect of angiotensin Ⅱ type 1 receptor on injury of renal tubular epithelial cells induced by high glucose - ZHA Dong-qing; YAO Tao; GAO Ping; WU Xiao-yan (Linchuang shenzangbing zazhi)
Objective To investigate the effect and possible mechanisms of angiotensin Ⅱ type1 receptor(AT1 R) on injury of renal tubular epithelial cells induced by high glucose. Methods The expression of AT1 R,AdipoR1,NF-κB,MCP-1,MIP-1 α,α-SMA,FN were detected by using western blot. The colocalization of AT1 R and AdipoR1 was detected by confocal microscopy. The dimerization of AT1 R and AdipoR1 was detected by immunoprecipitation. Results Compared with control group,the expression of AdipoR1 had no significant change and the expression of AT1 R was increased in rat renal tubular epithelial cells induced by high glucose. The expression of inflammatory factors as NF-κB,MCP-1 and MIP-1 α was increased in rat renal tubular epithelial cells stimulated with high glucose.Compared with control group,the expression of α-SMA and FN was increased in rat renal tubular epithelial cells stimulated with high glucose. The dimerization of AT1 R and AdipoR1 was formed in the rat renal tubular epithelial cells. And the AT1 R-adipoR1 dimerization was increased in the rat renal tubular epithelial cells induced by high glucose. Knockdown of AT1 R by siRNA inhibited the demerization of AT1 R-adipoR1,reduced the expression of inflammatory factors as NF-κB,MCP-1 and MIP-1 α,decreased the expression of α-SMA and FN in rat renal tubular epithelial cells induced by high glucose.Conclusions AT1 R promotes the inflammation and fibrosis of renal tubular epithelial cells induced by high glucose through dimerization of AT1 R-adipoR1.